An information leaflet for patients receiving treatment by intravitreal drug injections. Recommendations of the Expert Council on retinal and optic nerve diseases of the Association of Ophthalmologists, an All-Russian public organization - V. V. Neroev; S. A. Korotkikh; E. V. Bobykin; O. V. Zaytseva; A. B. Lisochkina; A. F. Brovkina; M. V. Budzinskaya; M. V. Gatsu; N. N. Grigoryeva; A. S. Izmaylov; E. V. Karlova; M. A. Kovalevskaya; et al. (Российский офтальмологический журнал)
The widespread introduction of intravitreal drug injections into clinical practice has highlighted a number of issues to be solved, including the risk of serious complications, the treatment burden on patients and the patient’s insufficient adherence to treatment, as well as a significant effect on the healthcare cost and effort. One of the ways to resolve the issues is to increase the patients’ awareness concerning the therapy they are about to receive, which contributes to the patients’ understanding of the details of treatment and enables them to make correct decisions. The best option of presenting such information to the patient is to provide them with a written document. The Expert Council on Retinal and Optic Nerve Diseases of the All-Russian Association of Ophthalmologists has developed, approved and tested an information brochure for patients who receive intravitreal injections. It offers brief information on what the procedure is, contraindications, details of preparation, and symptoms, both common ones and those requiring emergency assistance. The paper outlines the results of the study and presents a layout of an information leaflet for patients recommended for use in the Russian Federation.